2020
DOI: 10.2217/fmb-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine as a Potential Treatment for COVID-19

Abstract: Oral administration of NAC (600 mg/day) could function as a preventive measure, particularly in those repeatedly exposed to possible SARS-CoV-2 carriers (e.g., health workers). "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 15 publications
(24 reference statements)
0
74
0
2
Order By: Relevance
“…71 Clearly, the potential anti-COVID-19 mechanisms and properties of this thiol have to be substantiated in controlled clinical trials, some of which are now in progress. 12,72…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Clearly, the potential anti-COVID-19 mechanisms and properties of this thiol have to be substantiated in controlled clinical trials, some of which are now in progress. 12,72…”
Section: Discussionmentioning
confidence: 99%
“…11 By blocking ACE, NAC may provide protection from the deleterious effects of angiotensin II, a potentially useful activity in SARS-CoV-2 infection. 12…”
Section: Sars-cov-2 Binding To Cellsmentioning
confidence: 99%
“…It is notable that PhyCB, phase 2 inducers, melatonin, N-acetylcysteine, berberine, glucosamine, and zinc have already been suggested for use in the management of COVID-19 [ 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 ]. The NADPH oxidase-inhibitory activity PhyCB may have potential for up-regulating the type 1 interferon response to SARS-CoV-2 and other RNA viruses, and may also act to suppress the induction of tissue factor, a likely trigger for the thrombotic complications of COVID-19 [ 235 , 236 ].…”
Section: Pertinence To the Management Of Covid-19mentioning
confidence: 99%
“…Similar studies on N acetyl cysteine like N-acetyl cysteine as a potential treatment for COVID-19 by Rangel Mendez et al has shown positive results in the COVID-19 patients and explored the potential of the drug to help flatten the exponential contagion curve. 22…”
Section: Discussionmentioning
confidence: 99%